Analysis of millennial tourist satisfaction on Pasumpahan Island city of Padang - Husna, Rifdatul; Zengga, Zengga; Della Sari, Windy (SEAN Institute, 2024)
Pasumpahan Island is an island with white sand and a clear sea, interesting photo spots, and beautiful views from the top of the hill, making Pasumpahan Island attractive to tourists. Pasumpahan Island is currently being developed as a leading tourist attraction in West Sumatra Province and can help of the people earn more money in Sungai Pisang Village. From observation data and visits made by the author, it was found that there were visitors who felt dissatisfied when visiting Pasumpahan Island. They are dissatisfied with the lack of the bathrooms availability and the quality of the water. Analysis is the study's main goal millennial tourism satisfaction on Pasumpahan Island, Padang City. This type of research is a sort of quantitative descriptive research. data sources that are used for both primary and secondary data. Purposive sampling was utilized as the sampling technique in this study, with a total sample size of 100 respondents, and the millennial generation as the respondent criteria based on the age group above 19–41 years. Regarding the results of a questionnaire using a Likert scale, it shows that the analysis of millennial tourism satisfaction on Pasumpahan Island, Padang City, seen from the indicators of achieving tourists' desires according to expectations, has a percentage of 74%, which is at the interval limit of 1.76-250, namely the dissatisfied category, while the indicator of willingness to give to Pasumpahan Island, Padang City, has a percentage of 80%, namely at the interval limit of 2.5–3.25, it is in the satisfied category. Furthermore, the indicator of interest in returning to Pasumpahan Island, Padang City, has a percentage of 54% at the interval limit of 1.76-250, namely the dissatisfied category.